2015
DOI: 10.1073/pnas.1419312112
|View full text |Cite
|
Sign up to set email alerts
|

Reverse switching of surface roughness in a self-organized polydomain liquid crystal coating

Abstract: In this work we propose randomly ordered polydomain nematic liquid crystal polymer networks to reversibly generate notable jagged relief patterns at a polymer coating surface by light illumination. The domain size is controlled by the addition of traces of partly insoluble fluorinated acrylate. The photoresponse of the coating is induced by a small amount of copolymerized azobenzene monomers. Upon exposure to UV light, azobenzene undergoes trans to cis isomerization, resulting in a change in molecular order an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
127
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 39 publications
2
127
0
1
Order By: Relevance
“…Under illumination, the trans ‐azobenzene isomerizes and induces an anisotropic deformation of the liquid‐crystal network (Figure 1 c) 35. This photomechanical property has been used to switch surface roughness36, 37 and to transform twisted shapes before 13, 38, 39. In the artificial valves that we designed, the two sets of bars undergo different shape and size modifications upon activation of 1 .…”
mentioning
confidence: 99%
“…Under illumination, the trans ‐azobenzene isomerizes and induces an anisotropic deformation of the liquid‐crystal network (Figure 1 c) 35. This photomechanical property has been used to switch surface roughness36, 37 and to transform twisted shapes before 13, 38, 39. In the artificial valves that we designed, the two sets of bars undergo different shape and size modifications upon activation of 1 .…”
mentioning
confidence: 99%
“…[13] Different modes of motion arise with more complex molecular arrangements. For example, expansion of chiral nematic LCs along the helical axis has been utilized to create polymer coatings with photoswitchable topologies [14][15][16][17] and polymer films with macroscopic helical motion. [18] Additionally, polymer films with splay-bend configuration, in which LC-mesogens gradually change orientation throughout the film cross-section, have shown to exhibit inherently anisotropic bending as well as achieve significantly faster and larger bending when compared to uniaxially aligned films.…”
mentioning
confidence: 99%
“…This actuation can be reversed by exposing the material to visible (VIS) light or heat, which accelerate the cis azobenzenes to fall back to the trans state. The current consensus in experimental [5,[7][8][9] and theoretical studies [10][11][12][13] is that the amplitude of the photoinduced deformation is related to the statistical building up of molecules in the cis state. However, a recent experimental study [14] has revealed that this is only one side of the story.…”
mentioning
confidence: 99%
“…Photophysics model.-A two-light nonlinear penetration model is developed based on previous theoretical studies [12,15]. In Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation